Electrospinning of immiscible systems: The wool keratin/polyamide-6 case study. (5th August 2017) - Aluigi, Annalisa; Varesano, Alessio; Vineis, Claudia; Del Rio, Alberto
Abstract: Blends of wool keratin and polyamide 6 (PA6) have shown interesting adsorbent properties in filtration. In this work, the miscibility of keratin and PA6 was studied for the first time through rheological measurements of diluted blend solutions. In particular, the immiscibility between the two polymers in different blend proportions was observed by the segregation of phases in the cast films. Nevertheless, notwithstanding the immiscibility, we demonstrate here that homogeneous keratin/PA6 blend nanofibers can be obtained by electrospinning as a result of rapid solvent evaporation, where kinetic effects prevail on thermodynamic effects, thereby avoiding phase segregation. The obtained nanofibers have diameters ranging from 100 to 250 nm, depending on the experimental conditions. We show, through a principal component analysis (PCA) that the percentage of keratin represents the most important variable to determine nanofiber diameters. Collectively, this study represents a successful case of immiscible electrospinning system for production of useful nanofibers as adsorbent material for different applications. Graphical abstract: Highlights: Miscibility of wool keratin/PA6 blends and electrospun fibres were investigated in depth. Chemical structures and viscometric measurements revealed immiscibility between the two polymers in all blending ratios. Immiscibility was confirmed by the observation of segregation phases between polymers in the cast films. Due to kinetic effects, homogeneous nanofibers are obtained from the keratin/PA6 immiscible system, by electrospinning. The PCA analysis highlighted the keratin percentage, as critical variable which influences the nanofibers diameter.